Effect of Sodhananga Achasnehapana Followed by Virechana in the Management of Rheumatoid Arthritis: A Case Report (International Journal of Ayurveda and Pharma Research, 2023)
Rheumatoid arthritis is a chronic, progressive autoimmune arthropathy and characterized by bilateral symmetrical involvement of joints with some systemic clinical features. Treatment in allopathic medicine involves NSAIDS and steroids, which carry their own collateral burden of side effects in long term use. According to clinical features, described in Ayurveda, Vatarakta closely resembles with Rheumatoid arthritis. The study is done to find the effect of Sodhananga Achasnehapana with Guggutiktaka ghritha followed by Virechana with Nimbamrita eranda taila in Rheumatoid Arthritis. Methods: It is a simple random single case study done at Government Ayurveda College Panchakarma Hospital, Poojappura, Thiruvananthapuram. Here a case of Vatarakta (Vatakapahadikam) was treated with Sodhananga Achasnehapana with Guggutiktaka ghritha followed by Virechana with Nimbamrita eranda taila after Rukshana karma. Results: The treatment was effective in reducing the ESR, RA factor and CRP levels of the patient diagnosed with Rheumatoid arthritis. Conclusion: The case report shows that Ayurvedic treatment is potent and effective in the management of Rheumatoid arthritis. There was no adverse effect found in the treatment. Hence it can be concluded that RA can be effectively and safely treated by using the Chikitsa siddhanta mentioned in Ayurveda